2020
DOI: 10.1080/20013078.2020.1816710
|View full text |Cite
|
Sign up to set email alerts
|

Fusion protein engineered exosomes for targeted degradation of specific RNAs in lysosomes: a proof‐of‐concept study

Abstract: Therapeutically intervening the function of RNA in vivo remains a big challenge. We here developed an exosome-based strategy to deliver engineered RNA-binding protein for the purpose of recruiting specific RNA to the lysosomes for degradation. As a proof-of-principle study, RNA-binding protein HuR was fused to the C-terminus of Lamp2b, a membrane protein localized in both exosome and lysosome. The fusion protein was able to be incorporated into the exosomes. Moreover, exosomes engineered with Lamp2b-HuR succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Electron microscopy studies have revealed that exosomes measure 50-150 nm in diameter and have a "dish-like" or "cup-shaped" morphology. In addition, several surface exosomal proteins, such as the lysosomal protein Lamp2b, heat shock protein Hsp70 and others (18,19) that serve as diagnostic markers have also been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Electron microscopy studies have revealed that exosomes measure 50-150 nm in diameter and have a "dish-like" or "cup-shaped" morphology. In addition, several surface exosomal proteins, such as the lysosomal protein Lamp2b, heat shock protein Hsp70 and others (18,19) that serve as diagnostic markers have also been identified.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the engineered tLyp-1 exosomes presented high targeting efficiency in lung cancer stem cells and the encapsulated siRNA was able to knock-down the target gene of cancer cells. In another case, the RNA-binding protein HuR was fused to the C-terminus of Lamp2b to form engineered exosomes, which decreased the abundance of RNA targets possibly via lysosome-mediated degradation, especially when the exosomes were acidified (Li Z. et al, 2020).…”
Section: Genetic Engineeringmentioning
confidence: 99%
“…More recently, we and others have developed immortalization strategies guided by the mechanistic understanding of the pathways that contribute to producer cell (and EV) potency [ 108 , 109 ]. Other strategies aimed at altering the EV surface include the stable introduction of a transgene expressing a chimeric protein comprising the intracellular domain of a conserved EV-surface receptor such as CD63 [ 110 ] or Lamp2b [ 111 ], which is fused to the extracellular portion of a protein of interest.…”
Section: Therapeutic Roles Of Extracellular Vesiclesmentioning
confidence: 99%
“…Many of these defined factors include miRNAs, other small RNAs, and proteins [ 95 , 102 ]. For instance, some strategies exploit the ubiquitination pathway by tagging proteins of interest with various versions of a “ubiquitination” signal, which prompts efficient binding and EV loading by the trafficking protein Ndfip1 [ 111 ]. Another strategy for protein loading into EVs involves fusing the protein of interest with the trafficking domain of Nef1, an HIV lipid raft trafficking protein with the ability to sort proteins into vesicles [ 113 ].…”
Section: Therapeutic Roles Of Extracellular Vesiclesmentioning
confidence: 99%